Helicobacter pylori Eradication Causes Perturbation of the Human Gut Microbiome in Young Adults - Yap, TWC; Gan, HM; Lee, YP; Leow, AHR; Azmi, AN; Francois, F; Perez-Perez, GI; Loke, MF; Goh, KL; Vadivelu, J (Public Library Science, 2024)
Background Accumulating evidence shows that Helicobacter pylori protects against some metabolic and immunological diseases in which the development of these diseases coincide with temporal or permanent dysbiosis. The aim of this study was to assess the effect of H. pylori eradication on the human gut microbiome. Methods As part of the currently on-going ESSAY (Eradication Study in Stable Adults/Youths) study, we collected stool samples from 17 H. pylori-positive young adult (18-30 years-old) volunteers. The same cohort was followed up 6, 12 and 18 months-post H. pylori eradication. The impact of H. pylori on the human gut microbiome pre- and post-eradication was investigated using high throughput 16S rRNA gene (V3-V4 region) sequencing using the Illumina Miseq followed by data analysis using Qiime pipeline. Results We compared the composition and diversity of bacterial communities in the fecal microbiome of the H. pylori-positive volunteers, before and after H. pylori eradication therapy. The 16S rRNA gene was sequenced at an average of 150,000-170,000 reads/sample. The microbial diversity were similar pre- and post-H. pylori eradication with no significant differences in richness and evenness of bacterial species. Despite that the general profile of the gut microbiome was similar pre- and post-eradication, some changes in the bacterial communities at the phylum and genus levels were notable, particularly the decrease in relative abundance of Bacterioidetes and corresponding increase in Firmicutes after H. pylori eradication. The significant increase of short-chain fatty acids (SCFA)-producing bacteria genera could also be associated with increased risk of metabolic disorders. Conclusions Our preliminary stool metagenomics study shows that eradication of H. pylori caused perturbation of the gut microbiome and may indirectly affect the health of human. Clinicians should be aware of the effect of broad spectrum antibiotics used in H. pylori eradication regimen and be cautious in the clinical management of H. pylori infection, particularly in immunocompromised patients.